The non-indigenous medusa Blackfordia virginica (Hydrozoa, Leptothecata) in tropical Brazil: 50 years of unnoticed presence - Veloso Freire, Milena (2014)
Blackfordia virginica, a hydromedusa native to the Black Sea, has become established in a number of estuarine areas worldwide. In estuaries of northeastern Brazil, only a single published report, from the early 1960s, exists of the species and its establishment here has remained doubtful. On discovering specimens collected in the region at various times between 1987 and 2000, however, we hypothesized that this hydromedusa has long inhabited estuaries in the area while going unnoticed. The objective of this study was to investigate its occurrence in brackish waters of tropical northeastern Brazil over the past 50 years. In a search for specimens we found 1,759 individuals from estuaries of the Santa Cruz Channel (Itamaracá) and Capibaribe and Jiquiá rivers that had been collected between 1987 and 2000. In addition, an analysis of grey literature (Ph.D. theses) suggests that the species has been present in the Santa Cruz Channel for at least five decades. Results thus support the hypothesis that this non-indigenous species has been established in the region for several decades at least, and that it constitutes an exotic component of the community.